Changing Course: Reflections of Second-Career Teachers - Darrell Lee (Arizona State University, 2011)
This study examined the phenomenon of second-career teachers with specific emphasis on the motivating factors, common experiences, and reflections of the participants in this study concerning the decision to leave already established professions in order to pursue a career in teaching. The study also inquired into the process involved in professional preparation as well as in assimilating to the culture of schools. The participants in this study indicated several reasons for changing careers, such as the need for more meaningful work, a more flexible and family-friendly schedule, and the desire to share their experiences with the younger generation. Many of the participants also discussed a sense of religious calling. Hardships faced by second-career teachers are discussed, along with an examination of the strengths and weaknesses of teacher education programs as they relate to second-career teacher candidates. Reflections concerning the participantsâ current teaching practices are also examined.